Improvisasi Hardskill Relawan Muhammadiyah dalam Menangani Bencana Alam - Amin, Muhammad Khoirul; Astuti, Retna Tri; Margono, Margono (Universitas Muhammadiyah Yogyakarta, 2020)
Disasters caused both by nature or non-nature, have a negative impact on human life. The impact of a disaster can be minimized with the alertness of officers or volunteers during the emergency response. Muhammadiyah through Muhammadiyah Disaster Management Center (MDMC) has actively participated in risk reduction and disaster management. MDMC has thousands of volunteers from central to regional level, so there are always volunteers ready when a disaster occurs somewhere, both domestically and abroad. The volunteers that number in the thousands have unequal abilities and skills in managing disaster. Community service programs were implemented with the aim of narrowing the gaps in knowledge and skills of volunteers in disaster management. The disaster volunteer empowerment program was implemented at MDMC Koordinasi Area Magelang Barat (Koarmabar) or West Magelang Area Coordination. The program implementation was conducted using tutorial methods, group discussions, practices, disaster management simulations, evaluation, and post- program knowledge development assistance. The results of the implementation of the disaster volunteer empowerment program illustrate that the knowledge and skills of volunteers in disaster management have increased. The volunteers understand and are skilled in conducting triage, evacuation, transportation and trauma healing.